PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE AKTIVE KNOWLEDGE SHARING DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS X SMA DR. H. ABDULLAH AHMAD PGAI PADANG TAHUN PELAJARAN 2016/2017 (JURNAL LEMMA, 2017)
Abstract. The background of this research is understanding student’s mathematical concept in teaching learning process still low and the student less want to divisible the knowledge in learn. The purpose of this research is to know how is the development of understanding student’s mathematical concept and what is the understanding of student’s mathematical concept with apply Active Knowledge Sharing type along with quiz better than understanding student’s mathematical concept with apply convensional learning in class X SMA PGAI Padang 2016/2017 years. The kind of this research is experimental research with random plan toward subject. The population of this research is the students of X class SMA PGAI Padang. The technique of take the sample is random. Selected the X.2 class as experimental class and X.1 class as control class. The instrument that used in this research are quiz and the final test. According to quiz analysis found that understanding students mathematical concept after gived the treatment low experienced and increased on every meeting. Hyphotheses testing used t test one side resulted.  and 1.697 on . So that . So, acceptance hypotheses was understanding students mathematical concept with apply active knowledge sharing type along with quiz better than understanding students mathematical concept with apply conventional learning in class X SMA PGAI Padang 2016/1017 years.Key word: quiz, Active Knowledge Sharing , understanding mathematical conceptAbstrak. Penelitianinidilatarbelakangiolehpemahamankonsepmatematissiswadalam proses pembelajaran masihrendah dan siswakurang mau berbagi pengetahuan dalambelajar. Penelitianinibertujuanuntuk mengetahui bagaimana perkembangan pemahaman konsep matematis siswa dan untuk mengetahui apakah pemahamankonsepmatematissiswa dengan menerapkan model pembelajaran aktif tipe Active Knowledge Sharing disertai kuis lebih baik daripada pemahaman konsep matematis siswa dengan menerapkan pembelajaran konvensional di kelas X SMA PGAI Padang TP. 2016/2017. Jenis penelitian adalah eksperimendenganrancanganpenelitian random terhadapsubjek. PopulasipenelitianadalahsiswakelasX SMA PGAI Padang. Teknikpengambilansampel dilakukan secara acak. Terpilih kelasX.2sebagaikelaseksperimendankelas X.1sebagaikelaskontrol. Instrumen yang digunakan adalah kuis dan tes akhir.Berdasarkananalisis kuis diketahui bahwa pemahaman konsep matematis siswa setelah diberi perlakuanmengalami penurunan dan peningkatan pada setiap pertemuan.Pengujianhipotesismengggunakanuji-t satupihakdiperolehdan  pada , dengan demikian sehingga hipotesisditerima yaitu pemahamankonsepmatematissiswadenganmenerapkanstrategi pembelajaran aktif tipe Active Knowldge Sharing disertai kuislebihbaikdaripadapemahamankonsepmatematissiswayangmenerapkanpembelajarankonvensionaldi kelasX SMA PGAI Padang TP 2016/2017.Kata kunci: Kuis, Active Knowledge Sharing , pemahaman konsepmatematis